2018
DOI: 10.1111/jgs.15288
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Physical Conditions, Multimorbidity, and Mild Cognitive Impairment in Low‐ and Middle‐Income Countries

Abstract: These results highlight the need to investigate the underlying mechanisms linking chronic conditions and MCI and whether prevention or treatment of chronic conditions or multimorbidity can reduce the onset of cognitive decline and subsequent dementia, especially in LMICs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
106
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 99 publications
(113 citation statements)
references
References 48 publications
5
106
0
2
Order By: Relevance
“…Adjustment for country was done by including dummy variables for each country in the model as in previous SAGE publications [33,34]. All variables were included in the models as categorical variables with the exception of age and number of chronic conditions (continuous variables).…”
Section: Discussionmentioning
confidence: 99%
“…Adjustment for country was done by including dummy variables for each country in the model as in previous SAGE publications [33,34]. All variables were included in the models as categorical variables with the exception of age and number of chronic conditions (continuous variables).…”
Section: Discussionmentioning
confidence: 99%
“…There are some studies that have showed that the presence of particular aspects, or some diseases, in hypertensive population confers a greater risk of cognitive impairment. This is the case of hypertensive patients with depression (49,50), or hypertensive population with a worse economic situation (51). In general population, many others factors such as depression, educational level, socioeconomic status (rural areas, low income, less social participation), physical inactivity or unhealthy diet have also been related to the development of cognitive impairment (3,(52)(53)(54)(55).…”
Section: Other Factors Related To High Bp and Risk Of Developing Cognmentioning
confidence: 99%
“…24 We applied the identical algorithms used in previous SAGE publications to identify cases of MCI. [25][26][27] Briefly, individuals fulfilling all of the following conditions were considered to have MCI:…”
Section: Mild Cognitive Impairment (Outcome)mentioning
confidence: 99%
“…41 Nonetheless, a recent study with a longer follow-up period assessed 708 adults at six time points over a 20-year period and concluded that the strength and stability of the connections between handgrip strength and cognition indicate bidirectionality and/or third-factor causality. 42 With regard to thirdfactor causality, both lower muscle strength and cognitive impairment occur in concert with a higher risk for chronic diseases 43 and low physical activity participation 44,45 which are on their turn risk factors for further cognitive decline. However, the association between weak handgrip strength and MCI remained significant in our study even after controlling for chronic conditions, depression, and physical inactivity indicating that the relationship is likely to be explained by underlying biological mechanisms, which were not assessed in the current study.…”
Section: General Findingsmentioning
confidence: 99%